Effect of prepartum dietary energy source on goat maternal metabolic profile, neonatal performance, and economic profitability (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This work aimed at studying dietary energy supplementation effects during late pregnancy upon the metabolic status of does, as well as on the birth weight (BW), body temperature, and metabolic profile for their kids and the net economic profit.  Materials and Methods: Eighty pregnant does (Egyptian Nubian) were equally split into four dietary treatments; the control (CON) receiving basal diet, the basal diet with 200 gm corn starch and 100 gm of molasses /h/d added (MS), the basal diet with 300 gm/h/d of corn grains added (CG), and the basal diet with 300 gm/h/d of barley grains added (BG).  Results: Body weight and temperature of kids were significantly higher in MS and BG groups, respectively. The serum concentration of albumin (Alb), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels are significantly decreased. At the same time, urea and vitamin A increased dramatically in the BG group before giving birth. After birth, conversely, the serum concentration of albumin, AST, ALT, cholesterol, and vitamin A significantly increased with energy supplementation. Kids in the BG group show the most high level of albumin. Furthermore, all supplemented groups increased dramatically in vitamin A. The economic efficiency of the MS group, followed by the BG group, was significantly higher compared to the other treatments.  Conclusion: It is beneficial for Egyptian farmers to feed extra concentrate (especially barley) to the does during late gestation stages to produce healthy kids with optimal BW and body temperature, as well as to avoid metabolic disorders that may affect the does at this critical stage. Finally, it can be said that this dietary supplementation may also increases the profit margins of the farmers.J. Adv. Vet. Anim. Res., 7(3): 566-574, Sep 2020http://doi.org/10.5455/javar.2020.g454